2007
DOI: 10.1261/rna.525607
|View full text |Cite
|
Sign up to set email alerts
|

Using 5′-PTMs to repair mutant β-globin transcripts

Abstract: Trans-splicing has been used to repair mutant RNA transcripts via competition for the spliceosome using pre-trans-splicing molecules, or ''PTMs.'' Previous studies have demonstrated that functional PTMs can be designed for either 39-or 59-exon replacement, with a vast majority of the work to date focusing on repair of mutations within internal exons and via 39-exon replacement. Here, we describe the first use of trans-splicing to target the first exon and intron of a therapeutically relevant gene and repair th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…Such settings were reported for epidermolysis bullosa (COL7A1, KRT14, PLEC) (Murauer et al, 2010;Wally et al, 2010;Wally et al, 2008), Duchenne muscular dystrophy (Lorain et al, 2010), cystic fibrosis (Liu et al, 2002;Song et al, 2009), frontotemporal dementia with parkinsonism (Rodriguez-Martin et al, 2009), severe combined immunodeficiency (Zayed et al, 2007), spinal muscular atrophy (Coady et al, 2007), sickle cell anemia and ß-thalassemia (Kierlin-Duncan and Sullenger, 2007). First in vivo assays showed the functionality of SMaRT in a mouse model of spinal muscular atrophy (Coady et al, 2008;Coady and Lorson, 2010).…”
Section: Spliceosome Mediated Rna Trans-splicingmentioning
confidence: 77%
“…Such settings were reported for epidermolysis bullosa (COL7A1, KRT14, PLEC) (Murauer et al, 2010;Wally et al, 2010;Wally et al, 2008), Duchenne muscular dystrophy (Lorain et al, 2010), cystic fibrosis (Liu et al, 2002;Song et al, 2009), frontotemporal dementia with parkinsonism (Rodriguez-Martin et al, 2009), severe combined immunodeficiency (Zayed et al, 2007), spinal muscular atrophy (Coady et al, 2007), sickle cell anemia and ß-thalassemia (Kierlin-Duncan and Sullenger, 2007). First in vivo assays showed the functionality of SMaRT in a mouse model of spinal muscular atrophy (Coady et al, 2008;Coady and Lorson, 2010).…”
Section: Spliceosome Mediated Rna Trans-splicingmentioning
confidence: 77%
“…10,12 A later report indicated that ribozyme-mediated trans-splicing (*36%) was detected in 293T cells with co-transfection of a target plasmid (mutated b-globin intron 1 3¢ splice site) and ribozyme plasmid targeting the intron 1 (binding domain and b-globin). 11 Transsplicing is less efficient than normal cis-splicing, and reasonably high levels of trans-splicing efficiency are needed for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…In a cell line model with co-transfection of a target plasmid (b-globin gene) and an RTM plasmid (binding domain and c-globin cDNA), initially both trans-splicing events and b-globin expression were detected by the same RT-PCR reaction (data not shown), similar to previous reports using a ribozyme. [10][11][12] However, the ratios of DNA band densities between b-globin cDNA (target) and trans-splicing products were strongly affected by PCR annealing temperatures. To calculate the efficiency of trans-splicing precisely (trans-splicing events per b-globin RNA), a more reliable RT-qPCR method was established by using a 1:1 molecular ratio of control plasmid containing both the transsplicing sequence and the b-globin gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations